The Development Review on Light Cycle Oil Upgrading Technology to Fuels and Petrochemicals - Xia Liu; Laibin He (Chemical Engineering Transactions)
Light cycle oil (LCO) is a middle distillate produced in the fluidized catalytic cracking (FCC) unit with a high content of aromatics, high sulfur and nitrogen, and low cetane number, which cannot meet the requirements of diesel blending requirement under the China National VI standard regulation. Hydrogenation is an important technology for LCO upgrading and utilization. By combining hydrotreating (HDT) process, desulfurization and denitrification steps are carried out, and the aromatic hydrocarbons with more than two rings are partially converted into cyclo-alkylbenzene. Combined hydrocracking (HYC) steps, cyclohexane undergoes ring opening, cracking, and isomerization reactions, LCO can be upgrading to producing high quality fuels including high-octane gasoline, and chemical products including light aromatic hydrocarbon rich in benzene, toluene, and xylenes. With the development of upgrading technology, integrating heavy oil hydrogenation with selective catalytic cracking, LCO can produce aromatics, ethylene and propylene, which providing an ideal pathway to valuable petrochemicals from LCO. The upgrading utilization of LCO is an important technological choice for refining enterprises to take their own advantages to enhance valuable products and achieve sustainable development.